WARM WATER FOOT BATH THERAPY IMPROVING SLEEP QUALITY ON ELDERLY - ANIEK PUSPITOSARI (Jurnal Jamu Kusuma, 2021)
Background: Most of the elderly population suffer from sleep disorders such as difficulty initiating sleep, decreased total sleep time, sleep efficiency, transient arousal and waking up too early. This condition causes a decrease in the quality of sleep in the elderly. Several efforts can be made to maintain sleep quality in the elderly, one of which is by providing relaxation therapy. Relaxation therapy using warm water with a certain temperature will have a sopartificant effect and can overcome sleep disorders. This study aims to determine the effect of warm water footbath therapy on the sleep quality of the elderly. Methods: Quantitative research with a pre-experimental one group pretest-posttest research design with a sample of 17 elderly people in RW 8 Kemiri Kebakkramat Village. Intervention with the provision of water with a warm temperature with a volume of approximately 5 liters to soak both feet. Sleep quality is measured by the Pittsburgh Sleep Quality Index (PSQI) before and after 12 sections. The data analysis method uses the Wilcoxon Signed Ranks Test of SPSS. Results: Wilcoxon Signed Ranks Test results showed that sig. 0.000 < 0.05. The difference in the sleep quality score occurred after being given the hot water foot bath therapy (mean difference of 2.35). Conclusion: warm water foot bath therapy affects the sleep quality of the elderly. Stimulation from warm water makes the body more relaxed and accelerates the decrease in the activity of the Reticular Activating System (RAS), so that the elderly feel sleepy and fall asleep.